Integrated resin induction enhances Agarwood formation in Gyrinops caudata - AMILDA AURI; PETRUS ABRAHAM DIMARA; YUBELINCE YUSTENCI RUNTUBOI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Auri A, Dimara PA, Runtuboi YY. 2025. Integrated resin induction enhances Agarwood formation in Gyrinops caudata. Biodiversitas 26: 3758-3768. Natural agarwood formation occurs sporadically and unpredictably, making it difficult to achieve consistent quality and volume in commercial cultivation. This study aimed to investigate the synergistic effects of mechanical wounding, paraffin sealing, and biological induction using Acremonium sp. on agarwood formation in Gyrinops caudata. The investigation was conducted at an agarwood plantation in West Papua, Indonesia, using a split-plot design that incorporated various canopy pruning levels and four resin induction treatments. Additionally, quantitative and qualitative assessments of wood discoloration, aroma intensity, anatomical changes, and chemical composition were conducted over 6 months. The results of the integrated method, comprising mechanical drilling, biological inoculation with Acremonium sp., paraffin sealing, and 25% canopy pruning, resulted in the highest resinous wood area (694.2 mm²) and the greatest chemical diversity, with over 50 compounds identified via GC-MS. In contrast, untreated controls showed only 306.8 mm² of resin area and 15 compounds. "Integrated" in this context refers to the combination of physical wounding, microbial stimulation, and silvicultural stress designed to activate resin biosynthesis pathways synergistically.